Comparative studies on field emission properties of carbon-based materials - Chen, KH; Wu, JJ; Chen, LC; Wen, CY; Kichambare, PD; Tarntair, FG; Kuo, PF; Chang, SW; Chen, YF (My University, 2000)
Comparative studies on field emission properties of various carbon-related materials including diamond, amorphous carbon, SiCN films, SiCN nanorods, and carbon nanotubes are presented. While diamond is well known for its potential use in cold cathodes, the emission current of a hydrogen-treated diamond film is relatively small compared to that of amorphous carbon or diamond-like-carbon film. Meanwhile, carbon nanotubes have demonstrated large emission currents at much lower threshold voltages, showing their potential for applications. However, the emission from carbon nanotubes is subjected to significant decay under long-term operation. The emission current and long-term stability can be improved using a new SiCN compound with nanorod morphology. The effective barrier height and the held enhancement factor derived from the Fowler-Nordheim equation are discussed in this paper. (C) 2000 Elsevier Science S.A. All rights reserved.
Keywords: amorphous carbon; carbon-based materials; carbon nanotubes; diamond; field emission properties; SiCN films; SiCN nanorods